2013
DOI: 10.4236/csta.2013.21001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Chemical Vapor Deposition of TiO<sub>2</sub> Thin Films for Highly Hydrophilic Performance

Abstract: Titanium-oxide layer was grown on glass substrate by plasma-assisted chemical vapor deposition (PCVD) using oxygen gas plasma excited by radio-frequency power at 13.56 MHz in the pressure as low as 3mtorr at relatively low temperature below 400˚C, and studied on the crystallographic properties with the hydrophilic behavior comparing to the layer deposited by low-pressure chemical vapor deposition (LPCVD). Raman spectra indicated anatase-phase TiO 2 layer without amorphous-phase could be formed above 340˚C by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…These methods have been also employed to deposit TiO 2 using APP; among them, the PECVD technique is used most commonly [48]. The wide use of this technique is attributable to its many advantages, primarily its relatively simple and low-cost experimental set-up and its ability to deposit thin films even at low temperatures [49][50][51][52][53][54][55][56][57]. The general process of the PECVD technique to deposit TiO 2 employs a Ti-based precursor-TTIP is used most often-which is transferred by a carrier gas, typically an inert gas, and then mixed with a feed gas.…”
Section: Atmospheric Pressure Plasma-enhanced Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have been also employed to deposit TiO 2 using APP; among them, the PECVD technique is used most commonly [48]. The wide use of this technique is attributable to its many advantages, primarily its relatively simple and low-cost experimental set-up and its ability to deposit thin films even at low temperatures [49][50][51][52][53][54][55][56][57]. The general process of the PECVD technique to deposit TiO 2 employs a Ti-based precursor-TTIP is used most often-which is transferred by a carrier gas, typically an inert gas, and then mixed with a feed gas.…”
Section: Atmospheric Pressure Plasma-enhanced Deposition Methodsmentioning
confidence: 99%
“…Different types of discharges have been also applied. However, most researchers have used either an rf of 13.56 MHz [ 50 , 52 , 53 , 54 , 56 ] or microwave discharges [ 49 , 51 , 55 , 58 , 59 , 60 , 61 ] to ignite the plasma. Further, the thickness, morphology, crystallinity, and other properties of the grown films have been diverse in research findings as they depend largely on the deposition parameters.…”
Section: Atmospheric Pressure Plasma-enhanced Deposition Methodsmentioning
confidence: 99%
“…Previously, it was reported by FTIR studies for TTIP dissociation that atomic oxygen radicals supplied from oxygen remote-plasma enhance the dissociation of TTIP and the dissociation energy is decreased to 27.3 kJ/mol [17]. In contrast, the energy for the dissociation in the PCVD was 4.5 kJ/mol as shown elsewhere [13]. The significantly low dissociation energy in the PCVD comparing to the remote-plasma assisted deposition suggested that charged particles such as electrons and ions were also contributed to the dissociation.…”
mentioning
confidence: 95%
“…Schematic details of the apparatus was shown elsewhere [13]. DC-coil was settled around the bell-jar to induce DC-magnetic field during the deposition.…”
Section: Deposition Of Tio X Layermentioning
confidence: 99%
See 1 more Smart Citation